A Hybrid Self‐Powered Arbitrary Wave Motion Sensing System for Real‐Time Wireless Marine Environment Monitoring Application (Adv. Energy Mater. 7/2022). Issue 7 (17th February 2022) - Bhatta, Trilochan; Maharjan, Pukar; Shrestha, Kumar; Lee, Sanghyun; Salauddin, Md.; Rahman, M. Toyabur; Rana, S. M. Sohel; Sharma, Sudeep; Park, Chani; Yoon, Sang Hyuk; Park, Jae Yeong
Abstract : Wireless Wave Monitoring In article number 2102460, Jae Yeong Park and co‐workers successfully demonstrate a hybrid self‐sustaining arbitrary wave monitoring system capable of measuring wave motion parameters with adequate accuracy and sensitivity. The electromagnetic generators and self‐actuating triboelectric sensors work concurrently for wireless transmission of wave information without an external energy supply. The fully‐packaged device is expected to find applications in intelligent networks for smart wireless wave monitoring in the near future.